Validez y fiabilidad de la escala de participación de niños y adolescentes (CASP): una revisión sistemática - Elizabeth Roldán González; Andry Yasmid Mera Mamián; Ana Marcela Bolaños Roldán; Lina Giccela Suarez Muñoz; Paola Andrea García Marín (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Participation is defined as voluntary involvement in everyday life situations. The Child and Adolescent Participation Scale (CASP) has been used to assess this construct, with its validity and reliability reported in various countries.